2001
DOI: 10.1038/sj.onc.1204346
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements of minisatellites in the human telomerase reverse transcriptase gene are not correlated with its expression in colon carcinomas

Abstract: Telomerase activation is crucial in human carcinogenesis. The limiting component of telomerase, the catalytic subunit (hTERT), is undetectable in normal somatic cells but present in most tumor cells, including the earliest stages of colon carcinoma. The mechanisms involved in the dierential expression in normal and tumor cells are not understood. In normal cells hTERT expression is shut down by a repressor, and upregulation could be a consequence of cis-acting changes in the hTERT gene, making it resistant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
2
17
2
Order By: Relevance
“…No polymorphism was found for the minisatellite in intron 12 (data not shown). However, contrary to a previous report (Szutorisz et al, 2001), the 61 bp repeat in intron 2 was found to be polymorphic (Figure 3). Four alleles of hTERT-VNTR 2-2nd were found, ranging from 40 to 44 repeats with 44 repeats for the most common allele, with a corresponding degree of heterozygosity of 0.476.…”
Section: Vntr Polymorphisms Within the Htert Genecontrasting
confidence: 55%
“…No polymorphism was found for the minisatellite in intron 12 (data not shown). However, contrary to a previous report (Szutorisz et al, 2001), the 61 bp repeat in intron 2 was found to be polymorphic (Figure 3). Four alleles of hTERT-VNTR 2-2nd were found, ranging from 40 to 44 repeats with 44 repeats for the most common allele, with a corresponding degree of heterozygosity of 0.476.…”
Section: Vntr Polymorphisms Within the Htert Genecontrasting
confidence: 55%
“…This is in accordance with a previous study of a small set of breast cancers. 17 We could also demonstrate a significant correlation between increased hTERT gene copy number and aneuploidy. The relationship in colorectal cancer between p53 abnormalities and aneuploidy is well known 30,31 and aneuploidy and gene amplification is closely related.…”
Section: Discussionmentioning
confidence: 60%
“…17 Interestingly, amplification (or increase in gene copy number) of the hTERT gene at chromosome 5p15.33 has been demonstrated in a significant fraction of established cell lines and malignant tumors of different origin using FISH or differential PCR. [18][19][20] Whether this increased gene dosage also results in an increased hTERT RNA expression followed by upregulation of telomerase activity has not been clarified.…”
mentioning
confidence: 99%
“…The second intron of the hTERT gene contains a meiotically unstable minisatellite with several putative binding sites for c-Myc (Szutorisz et al, 2001;Wu et al, 1999). Size rearrangements of that minisatellite are not required for telomerase expression in colon carcinomas (Szutorisz et al, 2001). In 31 of 33 colon carcinomas that were heterozygous for the polymorphic minisatellite the 1 : 1 ratio of hTERT alleles was maintained, indicating that there had been no gene ampli®cation in these tumors.…”
Section: Possible Models Of Htert Regulationmentioning
confidence: 99%
“…We have found no evidence for rearrangements in the 5' flanking region and the 5' half of the gene (710 to +25 kb) screening a number of cell lines of divers origin. The second intron of the hTERT gene contains a meiotically unstable minisatellite with several putative binding sites for c-Myc (Szutorisz et al, 2001;Wu et al, 1999). Size rearrangements of that minisatellite are not required for telomerase expression in colon carcinomas (Szutorisz et al, 2001).…”
Section: Possible Models Of Htert Regulationmentioning
confidence: 99%